Korean red ginseng attenuates hyperglycemia-induced renal inflammation and fibrosis via accelerated autophagy and protects against diabetic kidney disease. (23rd May 2020) - Karunasagara, Shanika; Hong, Geum-Lan; Park, Se-Ra; Lee, Na-Hyun; Jung, Da-Young; Kim, Tae-Won; Jung, Ju-Young
Abstract: Ethnopharmacological relevance: Panax ginseng C.A. Mey. (Korean ginseng) has been widely used in traditional medicine to treat diabetes mellitus for thousands of years. It also plays a key role in health maintenance owing to its anti-oxidant and anti-fatigue properties, and is quite popular as a dietary supplement. Aim of the study: This study was designed to offer a complementary and alternative medicine to manage the diabetic kidney disease (DKD), which causes long-term damage to the renal structure. We also investigated the regulation of the autophagy mechanism, which is the underlying the pathogenesis of DKD. Materials and methods: The effect of Korean red ginseng (KRG) on DKD was evaluated using human kidney proximal tubular cells and streptozotocin (STZ)-treated Sprague-Dawley rat models. In vitro experiments were conducted to evaluate the proteins related to fibrosis and autophagy. This was followed by in vivo experiments involving rats treated with single intraperitoneal administration of STZ (60 mg/kg) and then with KRG solution orally for 4 weeks. Proteins related to renal injury, fibrosis, and autophagy were determined by immunoblotting. Hematoxylin and eosin (H&E), Periodic acid-Schiff (PAS), Sirius red, and immunostaining were processed for histological studies. Results: KRG diminished the levels of metabolic measurements and blood parameters. Western blotting showed a decreased expression of proteins, such as TGF-β1, KIM1, and AGE, which are responsible for renal inflammation, injury, and fibrosis. Histological studies also supported these results and revealed that the KRG-treated groups recovered from renal injury and fibrosis. Furthermore, the autophagy marker, LC3, was upregulated, whereas p62 was downregulated. The levels of proteins related to the autophagy mechanism, such as ATG7, increased, while mammalian target of rapamycin (mTOR) decreased with the KRG treatment and exhibited accelerated autophagy compared to the STZ alone group. Conclusions: KRG can suppress renal inflammation, injury, and fibrosis by blocking TGF-β1 activation and can induce cellular autophagy. Therefore, this study strongly suggests that KRG exhibits a renoprotective effect against the STZ-induced DKD. Graphical abstract: Image 1